Fault lines in the secondary education system in two Indian states - Rashmi Sharma (Indian Council for Research on International Economic Relations (ICRIER), 2020)
This paper, situated against the growing body of work that argues that adequate state capacity and robust public institutions are key for socio-economic development, examines the leading and supporting institutions of secondary education in two Indian states, Andhra Pradesh (AP) and Rajasthan. The paper is based on a field-based study of policies and 20 organizations, i.e, their structure, human resources and working style. Both states had organizations for school administration, programme implementation, academic support, conduct of examinations and education of drop-outs. However, activities related to academic support to schools such as curriculum design, textbook writing and teacher training, were split across several organizations, including those where these were not the core mandate. Moreover, there was excessive role splitting across organizations and inadequate organizational penetration in the field. The organizations lacked expertise in core areas, i.e. academic areas, educationally marginalized children and management issues. Employees had a perverse incentive structure, as promotions and slow and seniority-based, while good postings are obtained by pleasing political patrons. The working style was based on centralization and hierarchy, with limited emphasis on knowledge generation and analysis. There was continuous political interference and rent-seeking. The result was, fault lines in the system that constrained it in achieving goals. Deficient analysis and hierarchy-based functioning led to drifting rather than reasoned policies. Inadequate academic expertise meant that learning issues were marginalized, and the needs of under-privileged children were addressed only partially. Extreme centralization and hierarchy reduced the scope for substantive work and individuals, rather than systems became important. Patronage and rent-seeking led to the dominance of commercial interests.
Keywords: 330; State Capacity; Public Institutions; Secondary Education; Organizational Structure; Human Resources; Working Style; Fault Lines